Flexible Lithography: Marker Pen Lithography for Flexible and Curvilinear On‐Chip Energy Storage (Adv. Funct. Mater. 31/2015). (August 2015) - Jiang, Qiu; Kurra, Narendra; Alshareef, Husam N.
Abstract : Micro‐supercapacitors and other microscale energy storage devices can be fabricated on curvilinear surfaces using a simple marker pen. H. N. Alshareef and co‐workers show on page 4976 that the pen ink can be used as a sacrificial layer that selectively dissolves in some solvents to enable fabrication of devices without the need for masks. Traditional photolithography would be difficult to use on such curved surfaces.